Consumer Perceptions, Behaviors, and Knowledge of Food Waste in a Rural American State - Ahmed, Selena; Stewart, Alyssa; Smith, Erin; Warne, Teresa; Byker Shanks, Carmen (Frontiers in Sustainable Food Systems, 2021)
Understanding consumer knowledge, attitudes, and behaviors towards food waste is critical for informing evidence-based programs to advance sustainable food systems. A lack of knowledge regarding consumer food waste at the local level limits the ability to inform place-based solutions that are locally relevant. We administered an online survey to examine consumer perceptions, behaviors, and knowledge of food waste at the household level in Montana, a rural state in the United States. The majority of surveyed participants (58%) reported that they waste 10% or less of procured food. Almost half the participants (48%) are willing to take additional action to reduce food waste. Social factors including guilt and setting a good example were found to be greater motivators for reducing food waste compared to economic and environmental factors. Most survey participants (80%) perceive it would not be difficult to notably reduce their household's food waste. Overall, participants' reporting of their household's food waste quantity is lower than national quantities while their willingness to reduce food waste was higher than findings from a national survey. This study highlights the need for place-based solutions that are locally relevant to reduce household food waste towards enhancing the sustainability of food systems for supporting planetary health.